Looking beyond the obvious: How the National Literacy Act translates to adult education policy at state level - Hal Beder; Robert L. L. Dilworth (Adult Education Research Conference, 1994)
Using the National Literacy Act of 1991 as a reference point, this paper explores the interrelationship between federal and state adult education policy formulation and execution, with particular focus on the dynamics at state level.